Compensatory mechanisms to maintain glenohumeral joint stability in rotator cuff tears of differing severity during activities of daily living: A musculoskeletal model simulation study - Shobu Nakashima; Masayuki Kawada; Yasufumi Takeshita; Takasuke Miyazaki; Masafumi Fukuda; Hisanori Matsuura; Ryoji Kiyama (PLoS ONE, 2025)
Rotator cuff tears decrease glenohumeral joint stability; however, surrounding uninjured muscles could compensate for the reduced function of injured muscles to maintain joint stability. This study set out to analyze compensatory mechanisms that could maintain glenohumeral joint stability following rotator cuff tears of varying severity during normal daily life, using a musculoskeletal model simulation of rotator cuff tears. Fifteen healthy males performed 6 activities including shoulder flexion and abduction, contralateral shoulder reaching, head reaching, and lifting a 1 kg object placed on low and high shelves. Glenohumeral joint stability and scapulohumeral muscle forces were estimated using an intact model and 7 models with complex injuries to the supraspinatus, infraspinatus, and subscapularis muscles. Joint stability was quantified using the positional relationship between joint reaction force and the glenoid. Relationships between changes in glenohumeral joint stability and scapulohumeral muscle forces, in the different models, were analyzed. Glenohumeral joint stability decreased in all activities according to rotator cuff tear severity. Decreased glenohumeral joint stability was more pronounced with lower arm elevation angles and greater severity of rotator cuff tear. At this moment, increase in teres minor and long head of the biceps were observed in the rotator cuff tear models compared with the Intact model. Teres minor force increased in the isolated supraspinatus model during all activities, and long head of biceps forces increased in Flexion, Abduction, and Head reaching activities. These increases in muscle forces were significantly correlated with joint instability, indicating their contribution to stabilization of the glenohumeral joint. In conclusion, in rotator cuff tear models of differing severity, increased uninjured muscle forces compensated for decreased glenohumeral joint movement. Compensatory mechanisms differed according to the pattern and severity of rotator cuff tears, as well as activity type.